A utilização de sistemas de confinamento de areias em material geossintético para proteção costeira em Portugal - Maria de Lurdes Lopes (2016)
Sand-filled geosystems can effectively incorporate protection schemes along coastal stretches under erosion, with high vulnerability, but limited littoral urbanization, where management risks are of low to medium intensity. In recent decades, due to an increasing perception that the coastal interventions of the so called hard type in which the seawalls and the groynes that dominate along the northwest Portuguese coast are included have important functional limitations and generate negative impacts at the level of the global management of coastal sediments, new approaches are receiving more attention from the part of the governmental agencies, as well as other stakeholders. The Portuguese experience with sand-filled geosystems in coastal protection works is summarised in this paper, based on a number of case studies, together with results from Research and Development projects in this field. Those projects focused on the stability analysis of geosystems under wave loading and of the sediment dynamics around this type of structure, as well as on the development of a new technology with the industry, more adjusted to be applied under severe hydrodynamic conditions, namely those existing along the Portuguese West Atlantic coast